Kalpana Ram & Margaret Jolly (eds.): Matemities and Modernities. Colonial and Postcolonial Experiences in Asia and the Pacific - Dalsgaard, Line (Tidsskriftet Antropologi, 1999)
Colonial and Postcolonial Experiences in Asia and the Pacific. Anmeldes af Line Dalsgaard